Aplikasi Failure Mode Effect Analisys (FMEA) untuk Mempermudah Perawatan dan Perbaikan Sitem Pendingin Main Engine Di Kapal - Kurniawan, Ratna Dwi; M, Gerada; S, Rudi (Marine Science and Technology Journal, 2022)
The ship as a transportation at sea musthave the safety requirements issued by the competent authority. Extreme environments, and machine operations that run 24 hours non-stop must have a high level of reliability. Good and proper maintenance will make the ship's life long and provide economic value. Several tools to perform risk analysis are FMEA, as a tool for qualitative analysis can be used as a reference in carrying out maintenance and as a tool that makes it easier for crews to carry out analysis and maintenance to prevent failure. In this case study, it can be concluded that the activities carried out by the crew are in accordance with what the FMEA table has compiled, and it is proven that even though the ship is more than 30 years old, it is still operating normally. This can be seen from the KM Mitra Papua logbook.